Pengaruh Penggunaan Media Tutorial terhadap Hasil Belajar Tenis Meja pada Siswa Kelas V SD Negeri Begawat 01 - Dimas Baiqun Akfa Sentauri; Didi Muhtarom (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by students' low basic table tennis skills, particularly in the technical aspects of holding the racket, hitting the ball, and maintaining proper body position. This condition results in low student learning outcomes in physical education subjects, so learning media that can support the learning process more effectively are needed. One alternative media that can be used is tutorial media, because it has the advantage of presenting movements visually, systematically, and can be repeated according to student needs. The method used in this study was an experiment with a one-group pretest-posttest design. The research subjects were 20 fifth-grade students of Begawat 01 State Elementary School, selected using a total sampling technique. The research instruments included a practical test of basic table tennis skills, observation, and documentation. Data on student learning outcomes before and after the treatment were then analyzed to determine differences in ability. The results showed a significant increase in basic table tennis skills after the use of tutorial media. Students were able to improve their racket holding techniques, adjust their body position, and become more skilled at hitting the ball. In addition, the use of tutorial media also had an impact on increasing student learning motivation and participation in practical activities. The clearly displayed visualization of movements helped students understand the steps of basic techniques more quickly and effectively. The conclusion of this study is that tutorial media is proven to be effective in improving the table tennis learning outcomes of fifth grade students at Begawat 01 State Elementary School. The implications of this study emphasize the importance of utilizing innovative learning media to support the physical education learning process, so that learning objectives can be achieved more optimally.